Evaluation of Teachers' Professionality In Improving The Quality Of Madrasah Education In The Era Of Globalization - Purdiyanto Purdiyanto; Hadiwinarto Hadiwinarto (At-Ta'lim : Media Informasi Pendidikan Islam, 2020)
Abstract: Evaluation Of Teachers' Professionality In Improving The Quality Of Madrasah In The Era Of GlobalizationThe purpose of this study was to determine and evaluate the quality of madrasah education in the study of teacher professionalism in the era of globalization. The method uses a qualitative approach with the type of library research and data sources from books and journals about the quality of madrasah education and the professionalism of teachers in the era of globalization. The results in this study indicate that the quality of madrasah education in the era of globalization in the 21st century in the western, eastern and central parts of Indonesia has differences in its quality towards quality education attainment in accordance with the National Education Standards (SNP). Teacher professionalism is one of the main factors affecting the quality of education. Professional teachers must have the ability: (1) to master teaching materials and materials; (2) master and apply philosophy, methods, techniques and practices; (3) take advantage of the development of ICT to improve the quality of learning; (4) self-development and improving professional performance; and (5) increasing commitment to community service.Abstract: Evaluasi Profesionalitas Guru Dalam Meningkatkan Mutu Pendidikan Madrasah Di Era GlobalisasiTujuan penelitian ini untuk mengetahui dan mengevaluasi mutu pendidikan madrasah dalam kajian profesionalitas guru di era globalisasi. Metode menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan (library research) dan sumber data dari buku-buku dan jurnal-jurnal tentang mutu pendidikan madrasah dan profesionalitas guru di era globalisasi. Hasil dalam penelitian ini menunjukkan bahwa mutu pendidikan madrasah di era globalisasi abad 21 yang ada di wilayah Indonesia bagian Barat, Timur dan Tengah memiliki perbedaan dalam kualitasnya terhadap pencapaian pendidikan yang berkualitas sesuai dengan Standar Nasional Pendidikan (SNP). Profesionalitas guru merupakan salah satu faktor utama yang mempengaruhi mutu pendidikan. Guru yang profesional harus memiliki kemampuan: (1) menguasai materi dan bahan ajar; (2) menguasai dan menerapkan filosofi, metode, teknis dan praktik; (3) memanfaatkan perkembangan TIK untuk meningkatkan kualitas pembelajarannya; (4) mengembangkan diri dan meningkatkan kinerja profesional; dan (5) meningkatkan komitmen pengabdian dirinya di masyarakat.